Implications of the P5 on the moral action dimension at SDN 3 Depok Trenggalek - Almanik Dyan Permatasari; Sa’dun Akbar; Syarif Suhartadi (Himpunan Pengembang Kurikulum Indonesia, 2026)
Proyek Penguatan Profil Pelajar Pancasila (P5) is a vital instrument in the Kurikulum Merdeka for character strengthening, particularly the cooperation (gotong royong) dimension, which emphasizes collaboration and care. This study aims to analyze the implications of P5 on the formation of students' moral action, specifically within the cooperation dimension at SDN 3 Depok Trenggalek. The research employed a descriptive qualitative method. Data collection was conducted through direct observation of student actions, documentation of activities, and in-depth interviews with the principal, teachers, and parents. Data analysis included reduction, data display, and conclusion drawing with source triangulation validation. The results showed that P5 management encompassed design stages, facilitator team formation, and evaluation. The manifestation of moral action in the cooperation dimension was concretely realized through the